From the Shiftless to the Unemployed: Social Policy from the Perspective of the History of Ideas - Rákosník, Jakub (Dějiny – teorie – kritika, 2024)
This article focuses on the genesis of the concept of "unemployment". The concept as we understand it today took root at the close of the 19th century, at a time when the first – very tentative – forms of unemployment insurance began to appear. here, I am trying to capture the language used in the past to describe people who did not work, which of course was to influence the way society was to deal with such non-working people. Liberalism in the 19th century and the ideas on the nature and tasks of man in the world that were associated with it created an anthropological description in which the importance of material assistance was supplanted by the disciplining and moral edification of fallen individuals which may be found in pre-liberal practice in the age of European mercantilism. Classical political economics also had difficulties explaining unemployment scientifically. Under its influence particularly in the first half of the 19th century, attention was shifted to an individualising explanation of the origins of unemployment, situating it to a large extent within the sphere of individual responsibility. I stress here the discursive "invention" of unemployment as opposed to what is perhaps a more ingrained idea today: that unemployment simply derives from the objective economic conditions that hold under capitalism.